Influência da disponibilidade e consumo de frutos no comportamento agonístico e espaçamento interindividual de macacos barrigudos (Lagothrix cana) - Ferreira, Thiago Cavalcante (2018)
Group living animals, like most primates, benefit from a reduction in predation risk and an improvement in their potential to compete for food with other groups. However, gregariousness also increases intragroup food competition that can modulate within-group agonism and interindividual spatial patterns. We evaluated the influence of fruit availability and consumption (degree of frugivory) on the agonistic behavior and interindividual distance in two populations of Gray woolly monkeys living in forest fragments in southwestern Brazilian Amazonia. We recorded 165 intragroup agonistic interactions in a feeding context via the “all occurrences” method and 3,549 records of spacing via scan sampling. Fruit consumption presented a direct relationship with agonistic and spacing behavior, whereas our estimate of fruit availability was a good predictor only for spacing. Woolly monkey selection of food patches composed of trees with diameter at breast height almost fourfold than that of the trees found in the phenology plots might explain the lack of relationship between fruit availability and agonism. The proportion of time (50%) that woolly monkeys had no nearby (<5 m) neighbors is compatible with a strategy of reducing intragroup fruit competition by managing interindividual distances. In sum, we presented the first evidence of aggressive intragroup feeding competition in Lagothrix cana and demonstrate the influence of fruit availability and consumption on some aspects of the social system of woolly monkeys.